IMPLEMENTASI PERANGKAT LUNAK DENGAN PENERAPAN PENCARIAN RELATIF (HASH SEARCH) - Winarno Sri; Sumardi Sumardi Sumardi (Semantik, 2011)
Searching a list of values is a common task. An application program might retrieve a student record, bank account record, credit record, or any other type of record using a search algorithm. Some of the most common search algorithms are serial search, binary search and search by hashing. Search method (searching) there is a wide - range. Each - each method has advantages and disadvantages. One search method (searching), which has the efficiency of a better place is a relative search (Hash Search). Search relative (Hash Search) using the formula for doing the placement process and search data. Search relative (Hash Search) divided into 2 types, namely Hash Closed (Closed Hashing) and Hash Open (Open Hashing). On Closed Hash is possible more than one data has the same function value resulting in a collision (collision). How to cope with this collision can be done with some strategies, such as Linear Resolution (Linear Resolution), Overflow and Double Hashing.Keywords: hash search, linier resolusion, overflow, double hashing.